Avaliação da neutralização dos efeitos citotóxicos do ácido lipoteicóico em canais radiculares - Xavier, Ana Claudia Carvalho [UNESP] (2014)
The lipoteichoic acid (LTA) is a Gram-positive bacteria's virulence factor, which should be neutralized on endodontic treatment. The objective of this study is determining the effectiveness of biomechanical preparation performed with different auxiliary solutions and different intracanal medications in the neutralization of LTA in root canals. For this, 108 human teeth were sectioned and standardizing. After sterilization, the canals were inoculated with known amount of LTA solution. After contamination of specimens, they were subjected to biomechanical preparation through rotary system (BioRace) and divided into 9 groups, according the irrigating solutions (1% sodium hypochlorite, 2% chlorhexidine gel and 12% propolis glycolic extract) and intracanal medications (calcium hydroxide + physiologic solution; calcium hydroxide + 2% chlorhexidine gel; chlorhexidine gel 2 %). There were performed 3 sample collections from the root canals: after biomechanical preparation, after EDTA (3 min) and after intracanal medication (14 days). Held macrophage activation with the samples, which had its supernatant collected after 24 hours. This supernatant was used to investigate the production (TNF-α, IL-6, IP-10, MIP-1α and IL-1β) and G-CSF by enzyme linked immunosorbent assay (ELISA). According to the results, there was statistic difference between the groups. Sodium hypochlorite showed the best results on TNF-α, IL-6, IP-10, MIP-1α e G-CSF and propolis on IL-1β. In S3, all groups showed low indices. The sodium hypochlorite is the best irrigant in neutralizing cytotoxicity effects of LTA, and all protocols are efficient on neutralizing LTA cytotoxic effect